Direct measurement of the muonic content of extensive air showers between $$\mathbf { 2× 10^{17}}$$ 2×1017 and $$\mathbf {2× 10^{18}}~$$ 2×1018 eV at the Pierre Auger Observatory - A. Aab; P. Abreu; M. Aglietta; J. M. Albury; I. Allekotte; A. Almela; J. Alvarez Castillo; J. Alvarez-Muñiz; G. A. Anastasi; L. Anchordoqui; B. Andrada; S. Andringa; et al. (European Physical Journal C: Particles and Fields, 2020)
Abstract The hybrid design of the Pierre Auger Observatory allows for the measurement of the properties of extensive air showers initiated by ultra-high energy cosmic rays with unprecedented precision. By using an array of prototype underground muon detectors, we have performed the first direct measurement, by the Auger Collaboration, of the muon content of air showers between $$2× 10^{17}$$ 2×1017 and $$2× 10^{18}$$ 2×1018 eV. We have studied the energy evolution of the attenuation-corrected muon density, and compared it to predictions from air shower simulations. The observed densities are found to be larger than those predicted by models. We quantify this discrepancy by combining the measurements from the muon detector with those from the Auger fluorescence detector at $$10^{{17.5}}\, {eV} $$ 1017.5eV and $$10^{{18}}\, {eV} $$ 1018eV . We find that, for the models to explain the data, an increase in the muon density of $$38%$$ 38% $$± 4% (12%)$$ ±4%(12%) $$± {}^{21%}_{18%}$$ ±18%21% for EPOS-LHC, and of $$50% (53%)$$ 50%(53%) $$± 4% (13%)$$ ±4%(13%) $$± {}^{23%}_{20%}$$ ±20%23% for QGSJetII-04, is respectively needed.